Peranan media internet Arab dalam meningkatkan kemahiran mendengar dan membaca di kalangan pelajar Melayu: suatu tinjauan - Hassan Azhari, Abd Rauf (Universiti Putra Malaysia Press, 2005)
The purpose of this article is the use of websites in Arabic language, mainly "http://eyenoon.fares.net, http://www.sendbad.net/, http://www.alsaha.com". The researcher will compare those websites from the linguistic aspects and the acquisition information. In addition, the researcher will also focus on two languages skills such as listening and reading which can be accessed from the internet media. Browsing the selected websites such as http://www.islampedia.com/, http://islamway.com can greatly enhance these two skills. The researcher believes that the information gathered from the article will enable readers to develop ideas and knowledge in the study and teaching of the Arabic language in Malaysia, in lini od the multimedia development in era globalization.